Clostridium difficile Colonization Before and After Hospitalization in Children - (:unkn) unknown (AVES, 2021)
Background: Beginning in the early 2000s, Clostridium difficile infection has become a major health problem in the United States, Canada, and in most European countries and has not only increased in incidence but also the severity. There are 2 conditions for the development of C. difficile infection: disruption of the normal gastrointestinal flora, and exogenous ingestion of the microorganism. We aimed to study C. difficile colonization in hospitalized children. We identified 2 issues: (1) the relationship between risks before hospital admission and colonization on the first day of hospitalization and (2) the effect of the factors that patients are exposed to during hospitalization on the colonization status at discharge. Methods: Patients aged between 2 and 18 years who were hospitalized with various diagnoses were included in this study. C. difficile toxin A/B was investigated in the stool samples taken on the admission and discharge days. Results: One hundred six patients were included in the study, of whom 24.5% and 48.1% of hemato-oncology patients were positive for C. difficile toxin A/B. Antibiotic usage within 1 month preceding hospitalization and the presence of underlying disease impact the C. difficile colonization status on the first day of hospitalization. Conclusion: Toxigenic C. difficile colonization prevalence is high in hospitalized children, especially in the hemato-oncology patient group.
Keywords: Antibiotic; children; Clostridium difficile; colonization; toxin; RISK-FACTORS; INFECTION; INFANTS; ACQUISITION; DISEASE